Utility value of improving writing skills for adult basic education students - Martinez, Jennifer; Greenberg, Daphne; Puranik, Cynthia; Braasch, Jason Lawrence; Traga Philippakos, Zoi A.; MacArthur, Charles A.; Miller, Christine (Journal of adolescent & adult literacy, 2024)
Motivational research identifies utility value, or the importance of a learning task to future goals, as central to motivation to learn. This study analyzed survey data (N = 86) collected from adult literacy learners to examine their utility value of writing improvement in grammar and spelling skills, word processing skills, and planning, drafting, and revising skills. Findings revealed that participants had a high utility value of improving writing in all three skill areas and possessed a variety of underlying motivations, including obtaining further education, seeking future employment, and personal reasons. Participants' age, educational attainment, and reading levels showed relationships with utility value of improving grammar and spelling skills, and age showed an additional relationship to utility value of improving word processing skills. This work extends research on motivation in this population and supports the application of expectancy‐value theory to both adult motivation and writing motivation.